The Relationship between Osseous Changes of the Temporomandibular Joint and RDC/TMD Groups in CBCT Images - Mahrokh Imanimoghaddam; Azam Sadat Madani; Mohammad Reza Talebzadeh; Ali Bagherpour; Mona Alimohammadi (Mashhad University of Medical Sciences, 2014)
Abstract Introduction: Temporomandibular joint disorders (TMD) are the most common disorders of the jaw, and despite their clinical importance, they are not completely understood. This study was aimed to evaluate the changes of temporomandibular joint (TMJ) on cone beam computed tomography (CBCT) images in disc displacement vs. osteoarthritis of the TMJ. Methods: In this study, 45 patients, including 37 women and 8 men (13-89 years of age), were examined. The patients were selected based on RDC/TMD criteria and group I disorders were excluded from the study. Accordingly, group II consisted of 43 joints with jaw clicking or displaced discs, and group III comprised 46 joints with crepitus. CBCT images in sagittal, coronal, and axial sections were examined to assess osseous changes in terms of flattening, sclerosis, erosion, resorption, and osteophyte formation. Data were analyzed using statistical tests including the chi-square, Mann-Whitney, and Kolmogorov-Smirnov tests with the confidence interval of 95%. Results: Mann-Whitney test for the comparison of mean age between groups II and III was not statistically significant (p value=0.06). A significant differences was found between two (RDC/TMD) groups according to the prevalence of condylar erosion, resorption, and osteophyte (p